Digitalisasi Sistem Pembayaran dan Masa Depan Transaksi Keungan(Studi Pada Qris) - Gabriella Naomi Yaspis Siregar; Mawar Indah Julita Hutagalung; Melanie Putri Nduru (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
The digital transformation of payment systems has changed how society conducts transactions. This study aims to examine the role of QRIS and digital wallets in modern payment systems and their implications for efficiency, security, and financial inclusion in Indonesia. Using a descriptive-qualitative approach based on literature review, this research analyzes Bank Indonesia's policies, payment technology developments, and key challenges such as cybersecurity and the digital divide. The findings show that digitalizing payment systems through QRIS and digital wallets enhances transaction speed and convenience, but requires adaptive regulations and cross-sector collaboration to build an inclusive and sustainable digital financial ecosystem